2022
DOI: 10.1186/s12877-022-03250-w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of multimorbidity among older adults in Korea: a 10-year cohort study

Abstract: Background Due to the rapid growth of the older adult population, multimorbidity has become a global concern for an aging society. Multimorbidity has been associated with poor health outcomes, including low quality of life and a high risk of mortality, resulting in an overload of healthcare systems. However, multimorbidity incidence and its related factors are poorly understood among older adults. This study aimed to determine whether sociodemographic characteristics, lifestyle, and psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Increasing age has a significant effect on multimorbidity development. This result corroborates with previous studies that showed an increment of multimorbidity cases in the aging population [50][51][52] . This finding is likely to be associated with physical and functional vulnerabilities in the aging population 52 .…”
Section: Discussionsupporting
confidence: 93%
“…Increasing age has a significant effect on multimorbidity development. This result corroborates with previous studies that showed an increment of multimorbidity cases in the aging population [50][51][52] . This finding is likely to be associated with physical and functional vulnerabilities in the aging population 52 .…”
Section: Discussionsupporting
confidence: 93%
“…The study mentioned in the initial query found that literacy level, marital status, occupation, and family history were associated with multimorbidity. [ 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the older patient population has a higher prevalence of multimorbidity, characterized by the coexistence of multiple underlying health conditions [ 17 , 18 ]. The prevalence of one or more comorbidities was approximately 81% among older patients, with hypertension, diabetes, and cardiovascular disease being most common [ 14 ].…”
Section: Clinical Features and Common Comorbiditiesmentioning
confidence: 99%